Functionalization of colloidal nanoparticles with a discrete number of ligands based on a "HALO-bioclick" reaction. Issue 77 (2nd September 2020) - Garbujo, Stefania; Galbiati, Elisabetta; Salvioni, Lucia; Mazzucchelli, Matteo; Frascotti, Gianni; Sun, Xing; Megahed, Saad; Feliu, Neus; Prosperi, Davide; Parak, Wolfgang J.; Colombo, Miriam
Abstract : A recombinant HALO-GFP fusion protein was designed and isolated to demonstrate the feasibility of controlling the number and orientation of protein ligands to be conjugated on colloidal gold nanoparticles. Abstract : A recombinant HALO-GFP fusion protein was designed and isolated to demonstrate the feasibility of controlling the number and orientation of protein ligands to be conjugated on colloidal gold nanoparticles. AuNPs functionalized with exactly one or exactly two GFP molecules exhibited fully preserved functionality of the protein. The method is very straightforward and generally provides highly bioactive nanoparticle–protein conjugates.